THE JOURNEY TO SUSTAINABLE DEVELOPMENT VIA SOLAR ENERGY: A RECAP - Butkar, Umakant; Pokale, Navnath B.; Thosar, Devidas S.; Potdar, Satyajit Ramesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In addition to being a fantastic source of energy and environmentally friendly technology, solar energy is one of the most significant types of green and renewable energy. It greatly facilitates the achievement of sustainable development energy results. Because sunlight has such a large daily energy quantum available,It is an incredibly useful resource for producing electricity. To completely fulfill our energy needs, efforts are being made to improve both solar photovoltaics and concentrated solar power operations. In other words, the energy sector benefits and job needs are met when there is a installed capacity of solar energy operations in the same location internationally. This research looks at the application of solar energy, how it fits into the framework of sustainable development, and how employment is generally impacted by renewable energy sources. It offers understanding and analysis of solar energy sustainability, covering both environmentally friendly and financially successful development. Likewise, It has established a link between the advantages of solar energy operations and sustainable development by enhancing environmental conservation, creating jobs, and satisfying energy needs. Lastly, solar energy technology serves as a backdrop for the energy sector’s operations and provides an early look at future advancements in this area.